Enhancement of a solar photo-Fenton reaction by using ferrioxalate complexes for the treatment of a synthetic cotton-textile dyeing wastewater - Lucila I. Doumic (2015)
Biological, photo-Fenton (PF) and photo-Fenton mediated by ferrioxalate complexes (PF/Ferrioxalate) processes were examined for the degradation of a synthetic cotton-textile dyeing wastewater. Aerobic biological treatment had a negligible effect on discolouration whereas total organic content decreased mainly due to the biodegradation of acetic acid initially present in the wastewater. PF process yielded a fast and pronounced dissolved organic carbon concentration decay, mostly associated to the abrupt precipitation of Fe(III)organic complexes. The addition of oxalic acid limited iron precipitation, allowing mineralization of most organic contaminants. The influence of the different dyes and main dyeing auxiliary constituents of the synthetic textile wastewater on the PF and the PF/Ferrioxalate efficiency was systematically analysed. The suitability of combining PF/Ferrioxalate with conventional biological processes as a pre and/or post treatment was evaluated. This study highlights the potential of PF/Ferrioxalate reaction to mineralize the synthetic cotton-textile wastewater under appropriate experimental conditions, the best being: [Fe3+] = 40 mg L-1, iron/oxalate molar ratio = 1:3, pH = 4.0 and [H2O2] = 50-100 (1.5-2.9) mg L-1 (mmol L-1). At these conditions, the PF/Ferrioxalate treatment was carried out under natural sunlight in a pilot plant equipped with compound parabolic collectors.